The impact of tropical SST variability on the northern hemisphere circumglobal teleconnection pattern - Lin, Yen-Heng; Fosu, Boniface; Ikuyajolu, Olawale J. (Frontiers in Earth Science, 2023)
Tropical-extratropical teleconnection during boreal summer is characterized by a circumglobal teleconnection (CGT) pattern and is often considered as one of the major predictability sources of extratropical atmospheric circulation. The extent to which the summer circumglobal teleconnection pattern is remotely forced by tropical sea surface temperature (SST) variability remains to be elucidated. Here, we use a suite of pacemaker simulations from the Community Earth System Model (CESM1) to investigate the contribution of tropical sea surface temperature variability in the Eastern Tropical Pacific, Northern Atlantic, and Indo-Western Pacific to the summer circumglobal teleconnection circulation. We find that the variability of circumglobal teleconnection in the summer is dominated by the sea surface temperature variability in the Indo-Western Pacific and its remotely forced ENSO-like anomaly. As a result, the Indo-Western Pacific pacemaker experiment exhibits precipitation and surface temperature teleconnection patterns closest to the observed patterns in the Northern Hemisphere. A better understanding of such tropical-extratropical interactions can inform better seasonal forecasts and model development.